Section I-Introduction to analysis of seasonal cycles of water, carbon, and minerals through forest stands. - Waring, R. H.; Running, S. W.
The cycling of minerals through forest ecosystems is closely linked with those of water and carbon. Precipitation washes minerals from the atmosphere and deposits them on leaves and other surfaces. Water carries dissolved minerals into the soil where they are taken up by roots and transported in the transpiration stream.
Keywords: FOREST; ECOSYSTEMS